Методы исследования твердости поверхности материалов: учебное пособие - Никитенков Н. Н. Николай Николаевич; Шулепов И. А. Иван Анисимович; Степанов И. Б. Игорь Борисович; Тупикова О. С. Ольга Сергеевна (Томск, Изд-во ТПУ, 2014)
Заглавие с титульного экрана